Experimental and numerical analysis of HPTE on mechanical properties of materials and strain distribution - Omranpour, B.; Kulagin, R; Ivanisenko, Y; García Sánchez, Edgar (2017)
High Pressure Torsion Extrusion (HPTE) is a novel technique which has been recently introduced to the society of Nano-SPD researchers. HPTE exploits the deformation mechanics of HPT but in a larger scale using rod-shape samples and is capable of applying high values of strain to materials in one pass. This research aims to evaluate the effect of HPTE on mechanical properties of materials and also to study the effect of geometry of HPTE die on strain distribution in deformed samples by using Finite Element Method (FEM). Commercial pure Aluminium AA1050 was used for experimental work; and eccentric dies with parallelmisaligned channels were developed for evaluation by numerical modelling. Results of this research will help us better understand the effect of process parameters and also geometry of the die on materials.